Forest diversity and community dynamics along an altitudinal gradient of Ailaoshan Mountain (Yuanyang, Yunnan Province, China) - Li, Yuan; Zu, Yanqun; Wu, Bozhi; Gao, Guoqing; Guo, Fenggen (Journal of Environmental Engineering and Landscape Management, 2013)
In order to evaluate forest community diversity, the quantity of forest community succession along an altitudinal gradient from 1690 to 2016 m above sea level, the understanding of relationships between diversity and community dynamics, and data from sampling plots of forest communities were studied. Forest communities were mid-mountain moist evergreen broad-leaved forests on the southern slope of the Ailaoshan Mountain in Yuanyang County (near the Hani terraces) in Yunnan Province, China. The results showed that (1) the mean species richness, ecological dominance, and evenness (E) were 9.16, 0.31, and 0.27, respectively. The mean Shannon-Wiener Index and Coverage Weighted Foliage-Height Diversity Index were 0.84 and 0.41, respectively. (2) The mean live aboveground biomass (AGS) was 99.23 Mg/ha and the mean Composition Index (CI) was 182.17. Species diversity (including E, richness, and Shannon-Wiener Index), live AGS, and CI could be predicted by the mid-domain effect (MDE), which displayed a unimodal pattern against elevation. (3) Richness, E, Shannon-Wiener Index, and Coverage Weighted Foliage-Height Diversity Index increased with CI. Ecological dominance decreased with increased CI, following a quadratic relationship. Whittaker Index decreased with both increased CI and AGS, with a quadratic relationship. Much forest diversity could be explained by the MDE. However, forest dynamics were seriously disturbed by human activities. More attention should focus on increasing forest diversity in order to prevent the degradation of forest ecological functions thus resulting in threats to the sustainable development of the local ecological systems.